The Effectiveness of Family-Based Health Education on the Dash Diet (Dietary Approaches to Stop Hypertension) in Reducing Blood Pressure among Patients with Hypertension: A Literature Review - Putri Nurlia Angggraini; Abi Muhlisin (Indonesian Journal of Global Health Research, 2026)
The global rise in hypertension cases has made it one of the leading causes of morbidity and mortality from cardiovascular diseases. Nonpharmacological approaches using the DASH diet have been shown to be effective in controlling blood pressure; however, their implementation requires family involvement supported by systematic health education. This study aims to analyze the effectiveness of health education on the DASH diet for families in reducing blood pressure in patients with hypertension based on a literature review. This study employed a literature review method, searching for articles on PubMed, ScienceDirect, and ResearchGate published between 2020 and 2025. A total of 339 articles were identified, and following the PRISMA screening process, 8 articles were selected for analysis. Selection was conducted according to the PRISMA flowchart, resulting in eight articles meeting the criteria for descriptive analysis. The study findings indicate that providing DASH diet education involving family participation can help improve dietary patterns in hypertensive patients and contribute to controlling and lowering blood pressure. DASH diet education involving the family has been shown to contribute to changes in eating behavior and blood pressure control in individuals with hypertension.